Latentna katastrofa epoki atomu - Jerzy Franczak (Zagadnienia Rodzajów Literackich)
This article puts forward a comparative approach between the works of Tadeusz Różewicz and Inger Christensen in the context of the diagnosis of nuclear criticism. Briefly reconstructed variants of philosophical reflection are included in the conceptual framework created by Hans Ulrich Gumbrecht. The intention here is to capture the latent catastrophe, virtually existing, yet actually experienced. The historic novelty of the threat of collective suicide to the human species has turned into a specter that haunts all areas of our activity. Total nuclear war, according to Jacques Derrida, exists as a textual phenomenon, a “fairy tale.” It is so confused with reality that the pure reality of the atomic age cannot be distilled. Other philosophers write about the organized “system of disintegration” (Elsa Morante), about the system of deterrence, about the hyper-reality and simulacrality ( Jean Baudrillard), about the “supraliminal” phenomenon that shapes perception and thinking (Günther Anders). This nonevent provokes a permanent crisis for all institutions, problematizes notion of temporality, rules of rationality and subjective identity. Spider-Web Shield and Alphabet are seen here as artistic expressions of this experience… Różewicz creates a hybrid work and uses the collage technique. Ingersen, on the other hand, uses a formal rigor (abecedarium or alphabet book, alliteration) and a mathematical formula (Fibonacci sequence). They are both looking for an adequate form for a unique and elusive experience that determined the specific Stimmung (to add Gumbrecht’s terminology) of the post-war era.